Mercury, organic matter, iron, and sulfur co-cycling in a ferruginous meromictic lake. (November 2022) - Tisserand, Delphine; Guédron, Stéphane; Viollier, Eric; Jézéquel, Didier; Rigaud, Sylvain; Campillo, Sylvain; Sarret, Géraldine; Charlet, Laurent; Cossa, Daniel
Abstract: Mercury (Hg) speciation in natural waters is controlled by redox conditions and microbiological activity. Water columns of meromictic lakes have large and stable redox chemical and biological gradients that allow the investigation of many Hg chemical transformations. In this study, Hg speciation (elemental Hg = Hg 0, methylated Hg = MeHg) and partitioning between truly dissolved (<3 kDa), colloidal (<0.45 μm and >3 kDa), and particulate (>0.45 μm) fractions, were determined throughout a high-resolution water column profile in the ferruginous meromictic Lake Pavin (Massif Central, France) in July 2018. Total Hg concentrations (THg) in water ranged between 0.4 and 8.8 pmol L −1 . The particulate phase represented 10–70% of the THg, with a peak found in the mesolimnion associated with the particulate organic carbon maximum. In the mesolimnion, the colloidal fraction represented 12–68% of THg, and the highest value was found at the top of the sulfidic zone, whereas the truly dissolved Hg species (70 ± 9%) dominated in all the rest of the sulfidic zone. MeHg ranged from less than 10% of THg in the oxic mixolimnion to more than 90% in the anoxic monimolimnion. The Hg methylation was most active within the suboxic zone where iron and sulfate reduction are occurring. These results, associated with those of the partition of organic matter (OM), sulfur, and iron, in conjunction with thermodynamic calculations, allow us to present a conceptual scheme for the Hg cycle in the lake. Atmospheric Hg deposited onto surface waters of the lake is partially photo-reduced and returned to the air, another part is scavenged by biogenic particulate matter and conveyed at depth by settling organic material. Water stratification and redox changes create a sequence of reactions from oxic to ferruginous waters where Hg is successively (i) desorbed from particulate OM where mineralization occurs, (ii) adsorbed onto iron-oxy(hydr)oxides, (iii) desorbed where they dissolved, (iv) precipitate as HgS, (v) methylated, and (vi) reduced as Hg 0 in the deepest part of the lake. In brief, the (micro)biological uptake, OM, iron and sulfur recycling, through associated microbial consortia, control the Hg cycling in the Pavin waters. Graphical abstract: Image 1 Highlights: Lake Pavin is a permanently stratified ferruginous meromictic lake. Mercury (Hg) speciation and partition were examined along the water column. Hg exchange between solution, particles and colloids evolve with redox changes. Successive Hg methylation, precipitation (HgS), and reduction (Hg 0 ) with depth. Biological pump, and bacterial iron and sulfur recycling control the Hg cycle.